Economic restructure and reform of growth model in Vietnam - Vu Hung Cuong (Wieś i Rolnictwo)
Since the 1986 economic reforms known as ”Doi Moi” (All Round), the policies of Vietnam have been guided actively towards a more open and integrated economy within the world economy. After a period of rapid growth, Vietnam has a number of global recognized achievements. In 2010, Vietnam emerged as a lower middle income country based on World Bank rankings. Economic structures have been progressively modernised; social-economic infrastructure has improved significantly both in quantity and quality; some new and high technology industries have been introduced and developed. Recent research, however, indicates that the Vietnamese growth model has reached an end point and in this new context, the model reveals some weaknesses which require fundamental changes to occur. This need to reform the growth model becomes more urgent than ever to avoid a middle income trap and to improve competitiveness in order to actively cope with external risks in an international integration process, to step forward quickly, and to narrow the development gap with other countries in the region and the Global Economy. This paper focuses on analysing the weaknesses, shortcomings of the economic structure and current growth model in Vietnam with an aim to propose new directions and some key measures to implement economic restructuring in parallel with reforming the growth model for the period 2012–2020.